2001
DOI: 10.4049/jimmunol.167.7.3668
|View full text |Cite
|
Sign up to set email alerts
|

CD84 Functions as a Homophilic Adhesion Molecule and Enhances IFN-γ Secretion: Adhesion Is Mediated by Ig-Like Domain 1

Abstract: CD84 is a member of the CD2 subset of the Ig superfamily of cell surface molecules. Its cytoplasmic tail binds to Src homology 2 domain-containing protein 1A (signaling lymphocytic activation molecule-associated protein), a protein encoded by the X-linked lymphoproliferative disease gene. It is preferentially expressed on B lymphocytes, monocytes, and platelets. We show that it is also expressed on thymocytes and T cells. CD84 was positive on CD4−CD8− thymocytes, and its expression decreased with cell maturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
112
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(120 citation statements)
references
References 41 publications
2
112
1
Order By: Relevance
“…According to this concept, the known ligands of the CD2-related proteins are represented by one or another member of this molecular family. In particular, it has been shown that these molecular interactions are either heterophilic, such as CD2/CD58, CD2/CD48, and CD244/ CD48, or homophilic, such as CD150/CD150, CD84/ CD84, and CS1/CS1 [22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to this concept, the known ligands of the CD2-related proteins are represented by one or another member of this molecular family. In particular, it has been shown that these molecular interactions are either heterophilic, such as CD2/CD58, CD2/CD48, and CD244/ CD48, or homophilic, such as CD150/CD150, CD84/ CD84, and CS1/CS1 [22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Both heterophilic and homophilic interactions have been described between different members of the CD2 family [22][23][24][25][26][27][28]. We therefore explored the possibility that NTBA may recognize one or another member of this family.…”
Section: Ntba Mediates Homophilic Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following biotinylated anti-human mAbs were produced in our laboratory: CD84 (CD84.1.21), CD150 (SLAM.4), CD229 (HLy9.1.84) and CD244 (2B4.69) [9][10][11][12]. Biotinylated anti-human CD48 (99A) was provided by R. Vilella (Hospital Clinic, Barcelona, Spain) and CD150 mAbs (clones A12, 1B12, 10F5, 11G2, and 5G4) by Cox Terhorst (Harvard Medical School, Cambridge, MA, USA).…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…These cDNAs were cloned from either existing MGC clones or amplified from mixed-tissue human cDNA essentially as described (Collins et al 2004). Within this set of proteins are published negative interactions (Martin et al 2001;Kumaresan et al 2002;Falco et al 2004;Flaig et al 2004;Romero et al 2005), outlined with black circles in Figure 1D.…”
Section: Avexis Validationmentioning
confidence: 99%